Development of new rail repair profiles for different operating conditions - O. A. Suslow; I. V. Khromov (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. Currently, contact-fatigue defects prevail on rails with increased intensity of lateral and vertical rail wear. The authors consider it essential to develop rational repair profiles for sections with different track plan, as current repair profile regulations are insufficient, while taking into account the wheel and rail interaction in curves of different radii and straight lines.Materials and methods. Optimal rail head repair profiles were determined for different operating conditions by calculating the effect of wheel and rail profiles on the force impact on the track using the Universal Mechanism software. The rational parameters of the rail head tread surface were selected by mathematical analysis. The authors modeled variants of a conical wheel with two-point contact: a new wheel and a moderately worn profile. R65 type rail profiles were modeled: new profiles, R65 medium-grid, R65K.Results. The calculation and analysis data formed the basis for the recommended tread surface parameters to minimise the intensity of defect formation and rail wear. The authors developed rail head repair profiles for various operating conditions to be applied in grinding programmes.Discussion and conclusion. Grinding assignment criteria should include the basic parameters of the tread surface: central rolling radius R1 and arc length of the central radius d. The resulting repair profiles could be used to update the rail track grinding regulations.